Comment on “Strategic Information Management Under Leakage in a Supply Chain” - Tian, Lin; Jiang, Baojun (Management Science, 2017)
Anand and Goyal [Anand KS, Goyal M (2009) Strategic information management under leakage in a supply chain. Management Sci. 55(3):438–452] propose a horizontal differentiation model to study information leakage and demand signaling in a supply chain. The authors present a composite equilibrium consisting of separating and pooling outcomes in different parameter regions and claim that it satisfies the intuitive criterion. We show that their analysis for the pooling equilibrium has errors and also that all pooling outcomes are actually eliminated by the intuitive criterion. The positive note is that if the undefeated equilibrium or the lexicographically maximum sequential equilibrium refinement is adopted, a similar composite equilibrium will be achieved, which will lead to qualitatively the same results as in the original paper. This paper was accepted by Chris Forman, information systems.